Assessing health science students’ gaming experience: a cross-sectional study - Rodríguez-Roca, Beatriz; Calatayud, Estela; Gomez-Soria, Isabel; Marcén-Román, Yolanda; Cuenca-Zaldivar, Juan Nicolas; Andrade-Gómez, Elena; Subirón-Valera, Ana Belén (Frontiers in Education, 2023)
Background Digital gamification applied to university students enrolled in health-related degrees is considered an innovative and beneficial tool that complements traditional teaching. Objectives To analyze the enjoyment experience obtained by university students in the Faculty of Health Sciences and to know the gender differences after participating in a digital game. Design Cross-sectional descriptive study. Participants A total of 156 university students from the Faculty of Health Sciences, University of Zaragoza. Methods The activity of a digital game took place in the academic year 2021–2022 and was carried out as a teaching innovation project with the final approval of the University of Zaragoza. The tools used were the Spanish version of the Gameful Experience Scale and a self-administered questionnaire on satisfaction and suitability reported by the activity. Results A total of 156 students participated with an age of 21.2 ± 6.2 years. The highest score is the enjoyment dimension (4 ± 0.7), and the lowest score is the negative affect dimension (1.5 ± 0.9). Cronbach’s alpha for the whole Gameful Experience Scale was 0.95. There were significant differences in three dimensions of the Gameful Experience Scale: male students had more enjoyment than female students (p = 0.05), enjoyed a greater sense of domination (p = 0.01), and had fewer negative effects (p = 0.0). In the highest corresponding positions it was used for other topics such as learning (m 4.4; SD 0.5), motivation to learn (m 4.1; SD 0.8) or helping memorize concepts (m 4.4).4; SD 0.5). Conclusion Gender influences student satisfaction after carrying out a gamification activity, especially after a digital game. The dimensions in which gender differences were found were fun, absence of negative effects, and dominance.